LINGUOPRAGMATIC ASPECT OF APHORISMS IN ENGLISH AND UZBEK LANGUAGES - Arzimurodova, E’zoza (Educational Research in Universal Sciences, 2023)
The idiosyncrasies of how aphorisms operate in linguistic scientific discourse are examined in the essay. It has been determined that linguistic aphorisms are unique authorial statements that represent the subjective interpretation of linguistic concepts. Differentiating between scientific definitions of language words (i.e., the utterances of the primary nomination) and fictional definitions, which serve the function of secondary nomination, was one of the main goals of the study.